RICHNESS OF CONTENT OF ARTISTIC WORK AS SYNCRETISM KNOWLEDGE ABOUT A MAN AND WORLD(FROM EXPERIENCE OF TEACHING OF EDUCATIONAL COURSES "MAN AND CULTURE", "HISTORY OF THE UKRAINIAN CULTURE", IN VINNYTSIA NATIONAL TECHNICAL UNIVERSITY) - Strelbytskyi, M. P. (Visnyk of Vinnytsia Politechnical Institute, 2013)
On the basis of concepts of empathy and catharsis the richness of content of artistic(in particular literary) work as perceptual syncretism(connecting rational and irrational, intuitional constituent) knowledge is considered about a man, ethnos and humanity. Two analytical triads are substantiated, developed by the author of the article in the process of teaching of educational courses "Man and Culture", "History of the Ukrainian culture", in Vinnytsia National Technical University: gnosiological(autobiographic-authorial-epochal-eternal-common to all mankind) and axiological (ideology–ethos–instincts). Ethnic-national substance is thus attributed to both triads.